2017
DOI: 10.3892/ol.2017.6422
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidins from Vitis vinifera seeds induce apoptotic and autophagic cell death via generation of reactive oxygen species in squamous cell carcinoma cells

Abstract: Procyanidins can inhibit cell proliferation and tumorigenesis and induce apoptosis in human skin, breast and prostate carcinoma cell lines. Squamous cell carcinoma (SCC) of the skin is a common form of keratinocytic or non-melanoma skin cancer and is a deadly disease with a poor prognosis due to the ineffectiveness of therapy. The present study aimed to determine whether grape seed proanthocyanidin (GSP) may regulate different modes of cell death in the human SCC12 cell line. The present study found that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Proanthocyanidins also inhibit LPS-induced inflammation via inhibiting the mRNA expression of TNF-α and IL-1β and suppressing MAPK and NF-κB signal pathways [60]. Moreover, related studies demonstrated strong anti-proliferative properties of proanthocyanidins in squamous carcinoma cells, with increased apoptosis and autophagy [16,61]. Furthermore, proanthocyanidins were shown to be excellent inhibitors of VEGF and had in vitro and in vivo anti-angiogenic properties that affected angiogenesis by inhibiting of VEGF expression, endothelial cell migration, and vascularization [64,69,70].…”
Section: Characteristics and Clinical Applications Of Proanthocyanidinsmentioning
confidence: 97%
See 3 more Smart Citations
“…Proanthocyanidins also inhibit LPS-induced inflammation via inhibiting the mRNA expression of TNF-α and IL-1β and suppressing MAPK and NF-κB signal pathways [60]. Moreover, related studies demonstrated strong anti-proliferative properties of proanthocyanidins in squamous carcinoma cells, with increased apoptosis and autophagy [16,61]. Furthermore, proanthocyanidins were shown to be excellent inhibitors of VEGF and had in vitro and in vivo anti-angiogenic properties that affected angiogenesis by inhibiting of VEGF expression, endothelial cell migration, and vascularization [64,69,70].…”
Section: Characteristics and Clinical Applications Of Proanthocyanidinsmentioning
confidence: 97%
“…Proanthocyanidins belong to plant flavonoids, including catechin and epicatechin, and have antioxidant, anti-inflammatory, anti-angiogenesic, anti-proliferative, and immunomodulatory effects [16,[57][58][59][60][61][62][63][64][65]. Proanthocyanidins have been isolated from grapes, apples, metasequoia bark, cinnamon, aronia fruit, cocoa beans, bilberry, cranberry, black currant, and various other plants [16,66]. As powerful antioxidants and free-radical scavengers, proanthocyanidins have a wide range of application in the treatment for various OS-related complaints [67].…”
Section: Characteristics and Clinical Applications Of Proanthocyanidinsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also reported that cytotoxicity increases with the degree of polymerization and the percentage of galloylation of procyanidins and the gallate group seems to interfere with crucial cell functions; the galloylation appears to be a crucial structural feature defining the activity and toxicity of phenolic mixtures [ 35 ]. The cytotoxic activity of procyanidins in different types of cancer is, finally, well documented [ 36 , 37 , 38 , 39 , 40 ]. Therefore, these considerations agree with the results shown in this paper, justifying both the greater in vitro antioxidant activity and the most effective antiproliferative action seen for MBE.…”
Section: Discussionmentioning
confidence: 99%